Triage Sebagai Strategi Penanganan Pasien Di Instalasi Gawat Darurat - Abdul Rivai Saleh Dunggio; Fitriani. K Fitriani. K; Azmi Wijayanti (Barongko: Jurnal Ilmu Kesehatan, 2026)
The Emergency Department (ER) is a healthcare unit that handles patients with a variety of emergency conditions and requires rapid and appropriate treatment. The high number of patient visits with varying degrees of severity demands an effective treatment system, one of which is through the implementation of triage. Triage aims to determine the priority of patient care based on the level of severity to improve patient safety and service efficiency. This study aims to analyze the role of triage as a patient care strategy in the Emergency Department. This study used quantitative methods with an analytical design and a cross-sectional approach. The sample was emergency department nurses at healthcare facility X. Data were collected using questionnaires and observation sheets, then analyzed using the Chi-Square test. The results showed that good triage implementation was significantly associated with the effectiveness of patient care in the ER (p < 0.05).